Prevalence of H. Pylori Infection among Patients with Recurrent Gastric Ulcer in Arbil City - Bakhtyiar Shwan Azeez, Sana Rafat Yassin, Ayshan Rafat Yassin (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study’s goal is to identify the prevalence of H. pylori infection among patients with recurrent gastric ulcers in Arbil, Iraq. Study design: A cross-sectional study Place & duration of the study: From Oct 2021 to Feb 2022 in the private laboratories in Arbil city/Iraq. Methodology: A total of 83 patients with recurrent gastric ulcers were admitted to the private laboratories in Arbil city. Blood samples were collected for detection of anti-Helicobacter pylori antibodies IgG and IgA in patient serum samples by the serological method by Enzyme-linked immunosorbent assays. A special questionnaire sheet was designed and used for each patient subject. Results: Among 83 screened samples, the overall seroprevalence rate of H. pylori infection patients with recurrent gastric ulcer was 47 (56.6%). H. pylori infection was more common in female patients (59.1%) compared to male patients (53.8%). The rate of Helicobacter pylori infection was higher (84.2%) among the young adult-aged patient group (21-30) years, and (63.4%) in urban patients. A higher seropositive rate of H. pylori infection was among married patients (51.8%). Regarding marital status, most of the seropositive patients were among married patients (51.8%), (64%) among nonuse therapy, (56.7%) in the A blood group, (66.6%) among severe symptom patients, and (69.2%) among patients with a previous history of H. pylori infection respectively. Conclusions: Patients with recurrent stomach ulcers had greater levels of helicobacter pylori antibodies, which were linked to negative outcomes.